2017
DOI: 10.2134/jeq2016.02.0041
|View full text |Cite
|
Sign up to set email alerts
|

Application of Landfill Leachate Improves Wheat Nutrition and Yield but Has Minor Effects on Soil Properties

Abstract: Landfill leachates, which are potential pollutants, may also carry significant amounts of nutrients that can be recycled by plants. We assessed the nutritional status and yield of wheat ( L.) and properties of a Rhodic Kandiudult soil (depths of 0-10, 10-20, 20-40, and 40-60 cm) after 11 applications of landfill leachate over 4 yr. In the last application, wheat received 0, 32.7, 65.4, 98.1, or 130.8 m ha (875 mg L of nitrogen, N) of leachate and a positive control (90 kg ha of N as urea) 15 d after sowing. Ur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 37 publications
0
5
0
1
Order By: Relevance
“…The leachate contains rich organic matter, nitrogen, phosphorus, potassium and manganese, is a nutrient element of plants, and therefore, these nutrients may play a key role in the growth of plants when plants are exposed to lower levels of leachate. However, as the exposure concentration increases, various contaminated components in the leachate may enter and accumulate in plant cells, and therefore, the activity of several enzymes in chlorophyll biosynthesis may be suppressed due to inhibition of chlorophyll synthesis (Kuwano et al, 2017). Our results demonstrated that low levels of leachate increases chlorophyll content, which is due to the effects of nutrients of diaphragm.…”
Section: Discussionmentioning
confidence: 64%
“…The leachate contains rich organic matter, nitrogen, phosphorus, potassium and manganese, is a nutrient element of plants, and therefore, these nutrients may play a key role in the growth of plants when plants are exposed to lower levels of leachate. However, as the exposure concentration increases, various contaminated components in the leachate may enter and accumulate in plant cells, and therefore, the activity of several enzymes in chlorophyll biosynthesis may be suppressed due to inhibition of chlorophyll synthesis (Kuwano et al, 2017). Our results demonstrated that low levels of leachate increases chlorophyll content, which is due to the effects of nutrients of diaphragm.…”
Section: Discussionmentioning
confidence: 64%
“…Larutan lindi juga dapat berperan sebagai bahan pengurai penganti EM-4 dan MOL, karena mengandung mikroorganisme yang bermanfaat bagi tanaman dan juga sebagai bahan perombak. Selain mengandung mikroorganisme yang baik, lindi yang termodifikasi dengan waktu fermentasi juga mengandung nutrisi yang baik bagi tanaman (Kuwano et al, 2017).…”
Section: Pendahuluanunclassified
“…In the fall, the highest cob yields were achieved with the combination of PL+RP applied in a ratio of 2:1 (Figure 3C). The use of organic residues on agricultural soil can be an alternative for organic production for oat biomass nutrition, maize grain yield (Panchoni et al, 2016) and wheat nutrition (Kuwano et al, 2016).…”
Section: Times Of Application Of Pl+rp+m To the Maize Silage Cropmentioning
confidence: 99%